2016
DOI: 10.1016/j.tips.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

New Technologies for Elucidating Opioid Receptor Function

Abstract: Recent advances in technology, including high resolution crystal structures of opioid receptors, novel chemical tools, and new genetic approaches have provided an unparalleled pallette of tools for deconstructing opioid receptor actions in vitro and in vivo. Here we provide a brief description of our understanding of opioid receptor function from both molecular and atomic perspectives, as well as their role in neural circuits in vivo. We then show how insights into the molecular details of opioid actions can f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 93 publications
0
48
0
1
Order By: Relevance
“…Opioid receptors (ORs) are members of the class A (rhodop-sin-like) subfamily of GPCRs, which includes three subtypes, µ, δ and κ, and are important targets for analgesia [6] . Many studies have shown that the analgesic effect of μ-OR occurs through activation of the Gi signal, whereas the downstream β-arrestin pathway of the receptor can lead to constipation, respiratory depression, addiction and other adverse effects [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…Opioid receptors (ORs) are members of the class A (rhodop-sin-like) subfamily of GPCRs, which includes three subtypes, µ, δ and κ, and are important targets for analgesia [6] . Many studies have shown that the analgesic effect of μ-OR occurs through activation of the Gi signal, whereas the downstream β-arrestin pathway of the receptor can lead to constipation, respiratory depression, addiction and other adverse effects [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…including adenylyl cyclase inhibition and early ERK1/2 phosphorylation. Conversely, KOPr-mediated p38MAPK activation contributes to dysphoria and aversion Ehrich et al, 2015) as well as to sedation and motor incoordination (Bruchas and Roth, 2016). Furthermore, activation of this latter signaling pathway promotes partial sciatic nerve ligation (pSNL)-induced astrocyte proliferation and subsequent hyperalgesia and thermal allodynia (Clayton et al, 2009), and contributes to the modulation of potassium channel heterologous desensitization, possibly leading to antinociceptive tolerance .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, functional selectivity at opioid receptors has been intensely investigated in the last decade aiming at identifying more effective and safer analgesics, as many of the unwanted effects determined by MOPr or KOPr agonists are reduced or absent in b-arrestin-2 knock-out mice (Bohn et al, 2000;Raehal et al, 2005;Li et al, 2009;Bruchas and Roth, 2016). Therefore, increasing efforts have been devoted to developing functionally selective opioid agonists displaying a limited activation of arrestin-dependent signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations